STUDI TERHADAP ADANYA DUA VERSI RENTAK KUDO UNTUK ACARA PERNIKAHAN DI DESA RAWANG - Boyke Bobbi Andreas; Tulus Handra Kadir; Marzam Marzam (FBS Universitas Negeri Padang, 2013)
Abstract This research aimed to show the cause of the appearance two versions of art Rentak Kudo for wedding celebration in Rawang village. Method of research is qualitative. The collecting data : 1) Literature study 2) Observation 3) interview 4) Documentation 5) Photography. The analysis of data classified by using Primer Data and Sekunder Data, after separated then arranged sistematically. The result of research got that there are two versions of Rentak Kudo because the change os sense of community between each of Rentak Kudo versions have their own supporter. The appearance of the new Rentak Kudo because of the old Rentak kudo did not have standard entertain qualified of community nowadays. Kata Kunci: Studi, Rentak Kudo, Pesta Pernikahan,Rawang